Hyperbaric Oxygen Therapy in Children with Brain Injury: A Retrospective Case Series - Hajek, Michal; Jor, Ondrej; Tlapak, Jakub; Chmelar, Dittmar (International journal of medical sciences, 2025)
Introduction and Importance: Some experimental studies on brain injury associated with traumatic brain injury (TBI) and hypoxic-ischaemic encephalopathy (HIE) reveal a positive effect of hyperbaric oxygen therapy (HBOT). However, in clinical medicine, most of the scientific evidence available in the current literature relates only to TBI. Methods: The primary objective is to empirically assess the efficacy of HBOT in mitigating the symptoms of disability associated with brain injury in children, with a view to elucidating its therapeutic potential and clinical benefits. Outcomes: A total of 21 patients have been treated with HBOT. The mean age was 6±4.6 years. There were 12 cases (57%) of TBI, 8 cases (38%) of HIE and 1 case (5%) of ischaemic stroke. The mean initial Glasgow Coma Scale (GCS) at hospital admission immediately after accident was 3.3±0.9. The mean time from injury to HBOT was 5.2 ± 3.8 weeks. The mean number of HBOT exposures was 10±4.3. The mean GCS pre-HBOT was 10.7±3.7 and 12.3±3.4 (p=0.004) after post-HBOT, respectively. The mean Glasgow Outcome Scale (GOS) was 3.3±0.8 pre-HBOT, and 3.9±1.1 (p<0.001) after post-HBOT, respectively. Eighteen cases were included in response to HBOT assessment. Six cases (33%) were evaluated as large clinically significant response (CSR), 7 cases (39%) were evaluated as partial response with minimally important difference (MID). Five cases (28%) were evaluated as non-response. The results showed better response to HBOT in cases of starting HBOT up to 4 weeks (p=0.02) after the injury. There was no serious HBOT-related complication or injury. Conclusion: Results of our study demonstrate both clinical and statistically significant patient response to HBOT. Our data also suggest that the earlier HBOT started after diagnosis up to 4 weeks, the more pronounced patients' response to HBOT was achieved. The provision of HBOT to pediatric patients is feasible in large regional hyperbaric centers.
Keywords: Brain Injuries; traumatické poranění mozku; Female; Infant; dítě; předškolní dítě; Hypoxia-Ischemia, Brain; Brain Injuries, Traumatic; hyperbarická oxygenace; výsledek terapie; ženské pohlaví; Adolescent; lidé; Glasgowská stupnice kómat; poranění mozku; mozková hypoxie a ischemie; Treatment Outcome; Glasgowská stupnice následků; retrospektivní studie; Male; kojenec; Child, Preschool; Glasgow Coma Scale; Child; Glasgow Outcome Scale; mužské pohlaví; Hyperbaric Oxygenation; Retrospective Studies; mladiství; Humans